2019
DOI: 10.1002/ijc.32017
|View full text |Cite
|
Sign up to set email alerts
|

The role of microbiota in the development of colorectal cancer

Abstract: Colorectal cancer is the third largest cancer in worldwide and has been proven to be closely related to the intestinal microbiota. Many reports and clinical studies have shown that intestinal microbial behavior may lead to pathological changes in the host intestines. The changes can be divided into epigenetic changes and carcinogenic changes at the gene level, which ultimately promote the production and development of colorectal cancer. This article reviews the pathways of microbial signaling in the intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 119 publications
(202 reference statements)
1
72
1
4
Order By: Relevance
“…Furthermore, although the proportion of cases diagnosed before the age of 50 years increased in all zip code-level income quartiles, the highest proportion of young cases was in the highest income quartile. 26,27 A definitive causal link between antibiotic use and CRC has yet to be established, but a recent, large study from the United Kingdom did identify a strong association between oral antibiotic use in the previous 10 years and a diagnosis of colon cancer. 24 These NCDB data are thought-provoking in that factors typically associated with better access to health care (private insurance, urban geography, and white race) are associated with rising proportions of earlier onset colon cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although the proportion of cases diagnosed before the age of 50 years increased in all zip code-level income quartiles, the highest proportion of young cases was in the highest income quartile. 26,27 A definitive causal link between antibiotic use and CRC has yet to be established, but a recent, large study from the United Kingdom did identify a strong association between oral antibiotic use in the previous 10 years and a diagnosis of colon cancer. 24 These NCDB data are thought-provoking in that factors typically associated with better access to health care (private insurance, urban geography, and white race) are associated with rising proportions of earlier onset colon cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have correlated long-term antibiotic use with colorectal adenomas, 25 and multiple associative studies have correlated changes in the gut microbiome with the presence of CRC. 26,27 A definitive causal link between antibiotic use and CRC has yet to be established, but a recent, large study from the United Kingdom did identify a strong association between oral antibiotic use in the previous 10 years and a diagnosis of colon cancer. As expected, an analysis of clinical CRC characteristics stratified by age has shown that CRC detected in younger patients is more advanced with higher rates of regional and distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Gut microorganisms are involved in the development and progression of CRCs through many pathways such as through the induction of inflammation and biosynthesis of genotoxins. 23,24 Recent studies have suggested that the occurrence of CRCs is not only the function of a single microorganism, but also the result of the disruption of dynamic equilibrium of the gut microecology. 25,26 Microbial metabolites, such as short-chain fatty acids and secondary bile acids, act as an important part of gut microecosystem and are also involved in the occurrence of colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…When these bacteria also produce pathogenic pks, the chromosome can become unstable and cancers can occur [16]. Bacteroides fragilis releases an enterotoxin (BFT), activates the STAT3 signaling pathway, induces the production of Th17 and interleukin-17, and promotes colon cancer formation [17]. The BFT can rapidly induce the expression of SMO, promoting the production of ROS, and destroying the DNA of intestinal epithelial cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, BFT is able to amplify signaling via the Wnt and NF-κB signaling pathways, and leads to the release of pro-inflammatory substances. Fusobacterium nucleatum stimulates FadA, activates wnt/β-catenin/TLR4 signaling and upregulates oncogene expression [17], and Fusobacterium nucleatum can inhibit the activity of natural killer cells in the tumor microenvironment, leading to the occurrence of colorectal cancer [19].…”
Section: Introductionmentioning
confidence: 99%